2013
DOI: 10.1007/s12265-013-9467-y
|View full text |Cite
|
Sign up to set email alerts
|

Positioning of Inflammatory Biomarkers in the Heart Failure Landscape

Abstract: The clinical syndrome of heart failure is characterized by a systemic inflammatory response that contributes to end organ damage in the heart and circulation and can thus lead to worsening heart failure. The ensemble of inflammatory mediators that have been detected in heart failure patients include pro-inflammatory cytokines and their cognate receptors, as well as molecules secreted/released by macrophages (galectin-3 and pentraxin-3). Inflammatory biomarkers correlate with disease severity and prognosis acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 43 publications
3
66
0
2
Order By: Relevance
“…More recently, the contribution of a pro‐inflammatory state to the pathophysiology of HFpEF has been emphasized 6, 8, 17, 23, 31, 34, 35, 36, 45. In patients with ADHF, biomarkers reflecting activation of the renin‐angiotensin aldosterone system (RAAS) (plasma renin activity, aldosterone levels), oxidative stress (uric acid) and collagen synthesis (N‐terminal procollagen III) appear to be elevated to a similar extent in HFrEF and HFpEF 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the contribution of a pro‐inflammatory state to the pathophysiology of HFpEF has been emphasized 6, 8, 17, 23, 31, 34, 35, 36, 45. In patients with ADHF, biomarkers reflecting activation of the renin‐angiotensin aldosterone system (RAAS) (plasma renin activity, aldosterone levels), oxidative stress (uric acid) and collagen synthesis (N‐terminal procollagen III) appear to be elevated to a similar extent in HFrEF and HFpEF 33.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an effort to better characterize biomarkers in HF with preserved EF (HFpEF)2, 9, 31, 32). While inflammation plays a role in both HFpEF and HFrEF,33 there appear to be distinct differences in their pathogenesis 2, 34, 35, 36.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Recently, several studies suggested that circulating concentration of PTH was correlated with the severity of CHF and it could serve as a useful biomarker of the disease. 26 -28 In the present meta-analysis, our pooled results revealed that vitamin D supplementation was associated with a significant decrease in serum levels of TNF-α, CRP, and PTH.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the role of galectins in HIV infection. Galectin-3 (Gal-3) is secreted by macrophages; promotes eosinophil, neutrophil, and monocyte adhesion and recruitment, thereby enhancing inflammation [24]; and is a known marker of heart failure prognosis [25]. Gal-3 binding protein (Gal-3BP) is a soluble marker of M1-polarized macrophages [26], which are thought to be associated with inflamed, vulnerable plaques [27]; serum Gal-3BP levels have been found to be elevated in individuals with cancer or HIV infection [28,29].…”
mentioning
confidence: 99%